Executive-legislative relationship and its effect on political development in Nigeria - Chinweuba Godswealth, Ihemeje Chidiebere (2017)
The focus of this study is on the executive and legislative relationship in Nigeria’s Fourth Republic. The executive and legislative relationship in model government is crucial to any meaningful institution, inter-dependency, and harmony. It discusses the fundamental roles, personnel and constitutional powers of the executive and legislature. The executive-legislative relationship ought to promote harmony, checks and balances and political development. However, in Nigeria this relationship has witnessed suspicion, blackmail, intrigues and acrimony. The Military in Nigeria politics has relegated the legislative institution and allocated more powers to the executive which has contributed to executive interference in the legislative process. This has had negative implication on the independent of the legislative in Nigeria. Based on this, this study focuses on examining the factors influencing executive and legislative conflicts and harmony. It explains the extent of executive interference in the legislative functions and the implications of this relationship on political development in Nigeria’s Fourth republic. A qualitative method is used in the research and the data are collected mainly through document analysis and supported with interviews from twelve informants. The informants are selected among the executive ministers, legislators, academicians, and seasoned politicians. All informants are well informed with over ten years working experience. The interviews were tape-recorded and transcribed which supported document data analysis. This research used content analysis to descriptively analyze the results from documents and interviews. The importance of this study is to help administrators of the Nigerian State crafts on whose shoulder much is anticipated, to harmonious and interdependently work for the development of the nation. It is also important to help aspiring leaders to understand the working relationship between the executive and legislatures in a presidential setting. Evidence from findings showed that there is a sour and injurious relationship between the executive and legislative, and this has had a negative impact on political development. Again, the extent of legislative independence is crucial to a presidential system, but findings showed that executive supremacy over legislature has undermined the institution from successfully performing the roles of representing the people through law-making and oversight. This study emphasizes and recommends the need for a Constitution Drafting Committee and Constituent Assembly to totally draft a fresh Constitution for Nigeria to address the current unjust political structures, other than the constitution in use as handed down by the Military. This will promote adherence to the rule of law and prosecution of political offenders, and by so doing, the executive and legislative arms of government will confine themselves to their constitutional roles and be partners in progress in nation building and development.